Pengaruh Kebiasaan Mambaca Al-Qur’an Terhadap Perilaku Keagamaan Mahasiswa Pendidikan Agama Islam Angkatan 2020 Universitas Singaperbangsa Karawang - Putra Gustian, Tio; Yono (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The existence of Islamic boarding schools has played a big role in efforts to strengthen faith, increase piety, foster noble morals, develop the self-reliance of Indonesian society, participate in making the life of the nation intelligent through non-formal and formal education. Apart from that, Islamic boarding schools are a place to pursue education based on Islamic values as a whole, which is the hope for parents who are busy at work so they are unable to pay attention to how their children's daily lives are in terms of education, relationships and social life at all times, especially in the middle of school. The rise of teenage promiscuity is increasingly worrying and damaging to the future. The guidance provided at the Islamic boarding school is not only in terms of formal education, but also guidance in how to behave in social life, one of which is the guidance given by mudabbir as a guide appointed by the Islamic boarding school to be a foster parent while at the Islamic boarding school so that the students can adapt. , live independently, and carry out their social functions well. The aims of this research 1). To find out how mudabbir guidance strategies are in forming the independent character of students at the Miftahul Huda Islamic Boarding School, Bogor. 2). To determine the supporting and inhibiting factors for mudabbir guidance strategies in forming the independent character of students at the Miftahul Huda Islamic Boarding School, Bogor. The method used in this research uses descriptive research with a qualitative approach. The results of this research first show that the mudabbir guidance strategy in forming an independent character can be seen using exemplary education and supervision in the Tri Center for Education and Concept 6A for managingthe routine life of students. The two supporting factors are: Mudabbir's commitment and dedication, structured activities, education and spiritual formation. The inhibiting factors for the strategy of building the students' independent character are: The background of the students and their parents and the students' resistance to change.